2015
DOI: 10.4103/1947-2714.168669
|View full text |Cite
|
Sign up to set email alerts
|

Eighth joint national committee (JNC-8) guidelines and the outpatient management of hypertension in the African-American population

Abstract: Background:Hypertension is a common medical disease, occurring in about one third of young adults and almost two thirds of individuals over the age of 60. With the release of the Eighth Joint National Committee on Prevention, Detection, Evaluation, and Treatment (JNC-8) guidelines, there have been major changes in blood pressure management in the various subgroups.Aim:Optimal blood pressure management and markers of end-organ damage in African-American adult patients were compared between patients who were man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 18 publications
0
23
0
5
Order By: Relevance
“…A CDS developed in New York provides dental hygienists with assessments and recommendations for screening of chronic, systemic conditions such as hypertension and diabetes . As vital signs such as blood pressure are measured and recorded, the CDS provides assessments of personalized disease risk and prompts for referral to a specialist in appropriate situations as established by the current hypertension management guidelines . Another CDS was developed by Machado et al for use in dental trauma management and was found to improve adherence to evidence‐based guidelines in both dental students as well as experienced pediatric dentists .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A CDS developed in New York provides dental hygienists with assessments and recommendations for screening of chronic, systemic conditions such as hypertension and diabetes . As vital signs such as blood pressure are measured and recorded, the CDS provides assessments of personalized disease risk and prompts for referral to a specialist in appropriate situations as established by the current hypertension management guidelines . Another CDS was developed by Machado et al for use in dental trauma management and was found to improve adherence to evidence‐based guidelines in both dental students as well as experienced pediatric dentists .…”
Section: Discussionmentioning
confidence: 99%
“…80 As vital signs such as blood pressure are measured and recorded, the CDS provides assessments of personalized disease risk and prompts for referral to a specialist in appropriate situations as established by the current hypertension management guidelines. 81 Another CDS was developed by Machado et al for use in dental trauma management and was found to improve adherence to evidencebased guidelines in both dental students as well as experienced pediatric dentists. 82 The use of CDS for tobacco abuse screening and interventions has been found to improve both provider adherence to current evidence and patient outcomes.…”
Section: How To Use Datamentioning
confidence: 99%
“…The blood pressure was measured according to the World Health Organization (WHO) (17) using an electronic sphygmomanometer on the right arms of participants in a sitting position, after at least 5 minutes of rest. Hypertension is defined as systolic blood pressure value ≥140 mm Hg and/or diastolic blood pressure value ≥90 mm Hg or normal blood pressure in people on antihypertensive therapy (18). Serum creatinine was measured by the Jaffé kinetic method.…”
Section: Definitionsmentioning
confidence: 99%
“…Hypertension was defined as systolic blood pressure ≥140 mmHg and/or diastolic blood pressure ≥90 mmHg or lower than 140/90 mmHg in patients on antihypertensive therapy [6].…”
Section: Operational Definitionsmentioning
confidence: 99%